2019
DOI: 10.1097/md.0000000000015348
|View full text |Cite
|
Sign up to set email alerts
|

A novel AVPR2 missense mutation in an Asian family with inherited nephrogenic diabetes insipidus

Abstract: Rationale:X-linked nephrogenic diabetes insipidus (NDI) is a rare inherited disease, and is characterized by renal resistance to arginine vasopressin (AVP). Its diagnosis can be clinically challenging. The application of molecular genetic analysis can provide a rapid and definitive diagnosis.Patient concerns:A 75-year-old woman presented with recurrent nausea and vomiting was admitted to the Department of Gastroenterology. The patient had a strong family history of polydipsia and polyuria. Sequencing analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Oral disintegrating DDAVP was effective in the present case of partial congenital NDI, which was due to an AVPR2 gene mutation, and reduced urine output and water intake by approximately 30%. Previous studies reported a similar efficacy for nasal and oral DDAVP, which decreased urine output by 30-50% (4,6,8). Six AVPR2 mutations, p.A37P, pD85N, p.V88N, p.R104C, p.Y128S, and p.T164C, are associated with the response to high-dose DDAVP (4,7,8,10).…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Oral disintegrating DDAVP was effective in the present case of partial congenital NDI, which was due to an AVPR2 gene mutation, and reduced urine output and water intake by approximately 30%. Previous studies reported a similar efficacy for nasal and oral DDAVP, which decreased urine output by 30-50% (4,6,8). Six AVPR2 mutations, p.A37P, pD85N, p.V88N, p.R104C, p.Y128S, and p.T164C, are associated with the response to high-dose DDAVP (4,7,8,10).…”
Section: Discussionmentioning
confidence: 64%
“…Previous studies reported a similar efficacy for nasal and oral DDAVP, which decreased urine output by 30-50% (4,6,8). Six AVPR2 mutations, p.A37P, pD85N, p.V88N, p.R104C, p.Y128S, and p.T164C, are associated with the response to high-dose DDAVP (4,7,8,10). High-dose DDAVP was also reportedly effective in patients with partial congenital NDI with AQP2 gene mutations (10,14).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Males with AVPR2 mutations are symptomatic, whereas heterozygous females are usually asymptomatic [Celebi Tayfur et al, 2018]. However, some heterozygous female carriers have been reported to have NDI; this may be due to random inactivation of the X chromosome [Zhang et al, 2019]. By binding AVPR2, AVP can activate Gs/adenylate cyclase and then regulate the water channel AQP2 in renal tubules and collecting ducts, and finally the concentration of urine [Caletti et al, 2014].…”
Section: Discussionmentioning
confidence: 99%